ON SHADOW AND FORM: KOREAN NATIONALISM’S DIGRAPHIC CONFLICT - Strnad, William (International Journal of Korean Humanities and Social Sciences, 2016)
This paper is an examination of the many points of intersection between Korean nationalism in both Koreas, and Chinese characters (Hanja), as well as a contextualization of the historical and, at times, antithetical relationship or binary consisting of Hanja and Han’gŭl (Chosŏn’gŭl). Emerging from liberation the two Korean states over the next several decades would “engage” Hanja with diverse and fluctuating positions and approaches at different times. These responses have ranged from the abolition of Hanja or the enforcement of Han’gŭl (Chosŏn’gŭl) exclusivity, to the re-establishment and strengthening of Hanja education. Koreans for over a century have responded to “issues of script” based on socially-created narratives. This phenomenon can be viewed through constructivist paradigms, or can be interpreted as implemented pragmatic policies exemplifying instrumentalist nationalism. This paper’s assertion is that Korea’s vacillating response regarding Korean nationalism’s digraphic conflict is eloquent of the complex confluences that formed Korean ethnic nationalism, and therefore, Korean national identity.